NoBodies: Transnational Im/Mobilities and Dis/Embodiment in the Orchards of Niagara-On-The-Lake, Canada - Lozanski, Kristin (ACME, 2023)
The production of fruit, vegetables, and other horticultural crops in Canada relies upon the embodied labour of migrant agricultural workers who plant, prune, and harvest these crops. Using a feminist geopolitical lens, I foreground the bodies of these workers as these bodies are situated at the intersection of everyday lived experiences and systems of capitalist production through, in this case, Canada’s Seasonal Agricultural Worker Program (SAWP). Drawing on workers’ experiences of their bodies in the context of the regulatory provisions of the SAWP, I highlight the contradictory disembodiment of agricultural workers at the same time that their bodies are necessary to provide the physical labour at the heart of fruit and vegetable production. The disembodiment of these workers is possible because of their status as racialized non-citizens: while Canadians can insist upon the recognition of their bodies, migrant agricultural workers cannot. The disjuncture between embodied labour and embodied subjectivities was exacerbated with the onset of the COVID-19 pandemic, which disproportionately affected on migrant agricultural workers – through their bodies – while in Canada. Given the relative safety afforded to those who held citizenship (and other permanent) status in Canada, I argue that the active disembodiment of migrant agricultural workers in Canada demonstrates the ways that embodiment is a privilege that is tightly bound to citizenship.